Traveling Masculinities on the Summit: Reappropriations and Disarticulations of Mountain Climbing Visions in "The Alps of Granada" (1868–1900). Issue 1 (2nd January 2019) - Cornejo-Nieto, Carlos
Abstract : Over the past decade geographies of high places and mountaineering have attracted increasing interdisciplinary interest, but many of these studies have focused on the Alps. Southern Mediterranean mountains, and the Sierra Nevada in particular, have largely remained out of these debates. This article interrogates the first Betic mountaineering by highlighting the significance of the print culture inspired from the physical interactions with the Sierra's summits. The article aims to contextualize the representations and narratives by the nineteenth-century foreign and local climbers within global discourses of European mountaineering, and to analyze the circulation of predominant visions of mountain climbing, shaped by the British Alpine Club. By drawing on the theoretical framework of "geographies of reading, " the article shows how archetypal narratives and conventional imaginaries of Alpine climbing traveled across time and space through different media, and how they were either reappropriated or disarticulated in the Sierra according to its specific geographical features and local audiences.